2012
DOI: 10.7314/apjcp.2012.13.5.2279
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Malaysian Medical and Pharmacy Students Towards Human Papillomavirus Vaccination

Abstract: Human Papillomavirus (HPV) infection is one of the most common sexually transmitted infections and oncogenic HPV is the main cause of cervical cancer. However, HPV vaccination is already available as the primary preventive method against cervical cancer. The objective of this study was to determine the level of knowledge, attitude and practice of HPV vaccination among Universiti Kebangsaan Malaysia (UKM) and Universiti Malaya (UM) students. This study was conducted from March until August 2009. Pre-tested and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 13 publications
(7 reference statements)
4
53
4
3
Order By: Relevance
“…Most of the respondents did not know that HPV is a common infection; The Centers for Disease Control and Prevention (CDCP) report that at least 50% of sexually active individuals will acquire an HPV infection at some point in their life (Li et al, 2009;Merzouk et al, 2011) but it does not mean all these attacked women will develop cervical cancer; This lack of understanding about HPV may cause unnecessary stress and alarm if participants are diagnosed with HPV in the future which indicates especial effort to improve this kind of detailed and important knowledge (Pruitt et al, 2005;Rashwan et al, 2012). On the other hand more than half of the participants (64%) were aware about its link with cervical cancer and said that Pap smear can help HPV diagnosis but we expected higher percentage of right answer in a society of medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the respondents did not know that HPV is a common infection; The Centers for Disease Control and Prevention (CDCP) report that at least 50% of sexually active individuals will acquire an HPV infection at some point in their life (Li et al, 2009;Merzouk et al, 2011) but it does not mean all these attacked women will develop cervical cancer; This lack of understanding about HPV may cause unnecessary stress and alarm if participants are diagnosed with HPV in the future which indicates especial effort to improve this kind of detailed and important knowledge (Pruitt et al, 2005;Rashwan et al, 2012). On the other hand more than half of the participants (64%) were aware about its link with cervical cancer and said that Pap smear can help HPV diagnosis but we expected higher percentage of right answer in a society of medical students.…”
Section: Discussionmentioning
confidence: 99%
“…Relevance between HPV and cervical cancer is the most important information that the public should be aware about which may not be completely understood even by the medical community (Howard et al, 2007;Villar et al, 2011;Rashwan et al, 2012); this is a good explain why knowledge and understanding of HPV are low among the general public and they are more likely to be confused about HPV (M, 2001). Vaccine introduction, approval and ensuing advertising campaigns may cover theses gaps in knowledge and shift physician behavior (Zarcadoolas et al, 2012) whereas there is not national programs of HPV education and vaccination for public in Iranian society and any studies.…”
Section: Knowledge and Attitude Of Iranian University Students Towardmentioning
confidence: 99%
“…A European study reported that only 17.7% of university students had heard about HPV (Lenselink et al, 2008). Slightly higher rates of awareness of HPV, approximately one-third, were reported from university students in the United States and Malaysia (Dell et al, 2000;Philips et al, 2003;Rashwan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…University students are not representative of young adults in general, and the cervical cancer screening attitude and practice may be different in other sectors of the population. Future studies of this nature should include knowledge, attitude and practice of Human Papillomavirus (HPV), the main cause of cervical cancer, vaccination (Ghojazadeh et al, 2012;Rashwan et al, 2012;Hoque and Ghuman, 2013).…”
Section: Discussionmentioning
confidence: 99%